‘and yes I said yes I will Yes’ - Caimbeul, Aonghus Padraig (Scottish Studies, 2017)
These thoughts were inspired by the following riddle: A young man asked a maiden, as she was at an open window, when she would go a walk with him; and he got the answer that follows: “When I shall have lifted the linen (or net), lowered the glass, and put the dead to bury the living.” He, thereupon, giving up hope, sailed to foreign parts; and, returning at the end of three years, he heard she was married to another, but was not at all happy. This grieved him, and, on going to see her, he got the solution of her statement, thus: “As soon as I would have lifted the linen off the table, shut the window, and smoored the fire; and that did not long delay me, though you were impatient.”